Research methods and methodologies in education - Arthur, James (Los Angeles SAGE, 2012)
"This straightforward and jargon-free book will provide students with the theoretical understandings, practical knowledge and skills they need to carry out independent research. The international contributors identify key research methodologies, data collection tools and analysis methods and focus on the direct comparisons between them. Each chapter sets out the strengths and weaknesses of a key research method by: identifying specific research designs; presenting a series of relevant data collection tools; highlighting which analytical methods can be used. The chapters cover the full range of methods and methodologies, including internet research, mixed methods, and ethnographic research. Additional online materials are also available including links to useful journal articles. This is a key book for M-level students and other postgraduates within Education and Educational Research Methods courses."--Cover p. [4].
Part I: Introduction to research methods and methodologies in education -- 1. Introduction : how this book can help you James Arthur -- 2. The nature of educational research - exploring the different understandings of educational research Robert J. Coe -- 3. Finding your theoretical position Michael Waring -- Part II: Basic principles and practice in conducting research -- 4. Design of empirical research Larry V. Hedges -- 5. Planning your research Laura Day Ashley -- 6. Conducting your research Robert J. Coe -- 7. Research impact and dissemination Marilyn Leask -- Part III: Key methods -- Dimension 1: Research designs -- 8. Action research Carol Munn-Giddings -- 9. Naturalistic research Rob Walker -- 10. Ethnographic and representational styles Ghazala Bhatti -- 11. Grounded theory Robert Thornberg -- 12. Visual methodologies Jenni Karlsson -- 13. Case study research Laura Day Ashley -- 14. Issues of truth and justice Ian Davies and Andrew Peterson -- 15. Surveys and longitudinal research Anna Vignoles -- 16. Statistical and correlational techniques Stephen Gorard -- 17. Secondary data Emma Smith -- 18. Impact evaluation Steve Higgins -- 19. Interventions : experiments Peter Tymms -- 20. A systematic review Mark Newman and Kelly Dickson -- 21. Mixed methods Gert Biesta -- 22. Philosophical research Richard Pring -- Dimension 2: Data collection tools -- 23. Observation-based research Michael V. Angrosino -- 24. In-depth interviews Carolyn L. Mears -- 25. Techniques to assist with interviewing Rosalind Hurworth -- 26. Focus groups and group interviews Anita Gibbs -- 27. Internet-based methods Rhona Sharpe and Greg Benfield -- 28. Doing blog research Axel Bruns and Jean Burgess -- 29. Documentary methods Gary McCulloch -- 30. Systematic reviews Carole Torgerson, Jill Hall and Kate Light -- 31. Questionnaires Peter Tymms -- 32. Measurement and validity Ronald K. Hambleton -- Dimension 3: Analysis methods -- 33. Software and qualitative data analysis Graham R. Gibbs -- 34. Statistical analysis tools Paul Connolly -- 35. Discourse analysis Elaine Vaughan -- 36. Media analysis Michael Atkinson -- 37. Visual methodologies and social change Claudia Mitchell -- 38. Grounded theory Michael Waring -- 39. Ethnography as epistemology Judith L. Green, Audra Skukauskaite and W. Douglas Baker -- 40. Biographical research methods Michael Tedder -- 41. Statistical hypothesis tests Michael Borenstein -- 42. Analysis of variance (ANOVA) H.J. Keselman and Lisa Lix -- 43. Multiple linear regression Stephen Gorard -- 44. Multilevel analysis Michael Seltzer and Jordan Rickles -- 45. Effect size Robert J. Coe -- 46. Meta-analysis Larry V. Hedges.
Keywords: Education -- Research -- Methodology; Education -- Research